19th Annual Fresno County Legal Secretaries Association Annual Bosses' Night Honoring Gaspar Magarian - Watkins, Howard::::::::: (1987)
Legal Tender band: Nado Talanoa on base guitar, Ken Fransen with mic doing vocals, Penny Schafer doing vocals, Mark Snauffer on drums, Jim Schafer on piano, and Robert Fishman on guitar